A QUESTIONNAIRE-BASED ONLINE SURVEY ON KNOWLEDGE AND AWARENESS OF ANAEMIA AMONG FEMALE HEALTH-CARE PROFESSIONAL STUDENTS IN TAMILNADU - DE, NIRMAN KANNA; S, DHANUSH; B, RESHMA; MAGDALINE, BETTINA LAVANYA; PACKIRISAMY, SUBBULAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to assess the knowledge and awareness about anemia among Female Health-Care Professional Students in Tamil Nadu. Methods: A cross-sectional study conducted in Tamil Nadu, from December 2021–February 2022. Permission was obtained from IEC; a well-organized questionnaire was executed with 20 items using the Google Forms. Pre-structured questions were pre-validated by Experts. Google form contains the details such as socio-demographic, awareness, and knowledge based questions. The correct answer was marked as aware and incorrect as unaware and has converted to percentage. The completed data were collected, entered in excel sheet and the results were analyzed with the proper statistical method. Results: A total of 340 responses received and among that only 50.52% of female health-care professional students were aware of anemia and 72.83% of female health-care professional students had adequate knowledge about anemia. Conclusion: A significant lack of awareness was observed in female health care students. This study highly suggests the provision of health education, which can be implemented through periodic educational interventions such as webinars, CME programs, and role-plays. This may acts to build a safe tool to create more knowledge and awareness.